The hunt for baby melanomas: a prospective study of the dermoscopy features on 100 small melanoma cases with in vivo surface diameters up to a maximum of 6mm. - John Pyne; Sarah MacDonald; Susan Beale; Esther Myint; Wei Huang; Simon Clark; Andrew Trang (Dermatology Practical & Conceptual, 2022)
Background:: Early diagnosis can improve melanoma prognosis. Dermoscopy can enhance early melanoma recognition.